Entre a lona e a parede urbana: a outra face da pintura paraense pela obra de Moacir Cardoso - Daniely Meireles do Rosário (2019)
This research arose from a constant practice of observing the cities of Pará and the means that the self-taught painter uses as a support, focusing on the outer wall. From the large amount of photographic records made between the municipalities located on the Belém to Bragança roads, through the 223 kilometers that make up the current Pará State Tourist Route, the statements and the theoretical approach employed fell on the external mural commissioned for decorative, advertising and artistic, operating culturally as an urban visual device that modifies the understanding of the medium and directs the understanding of art in the places where they are established. In the end, the analyzes focused on the trajectory and artistic production of Moacir Cardoso, a painter who for more than two decades created, through painting, visual representation modes of amazonian and bragantine culture, in a mix of references and symbols that made him one of the painters most fertile of the municipalities of the interior of northeastem of Pará. The theoretical framework employs authors who discuss urban painting as a sign situated in an amazonian cultural context, allied with a written content that suggests the enchantment for the place and the contemplation of the waters, daily life and forests.